Evaluasi Kinerja Komite Sekolah di Sekolah Dasar Negeri - Ristu Nursanti; Yari Dwikurnaningsih; Mawardi Mawardi (Universitas Kristen Satya Wacana, 2020)
The purpose of this study is to evaluate the School committees’ performance that include: 1) consideration of determining and implementing educational policies; 2) raising funds and other educational resources from the community; 3) supervision of education services; 4) following up on complaints, suggestions, criticisms, and aspirations for school performance in SD Negeri Tuntang 02. Data collection techniques used in this study were used technical triangulation and source triangulation. Technical triangulation conducted through interviews, observations, and also documentary studies. Researchers conducted observations, interviews, and documentary studies on the performance of School Committees in SD Negeri Tuntang 02. While in triangulation of sources, researchers conducted interviews with School Committees, Principals, and also teachers. Data analysis techniques used in this study was qualitative approach. The results of this evaluative study showed that the School Committee's performance in giving consideration to the determination and implementation of education policies in SD Negeri Tuntang 02 showed an achievement rate of 11/12 x 100% = 92%, so that it was included in the good category. School Committee performance in raising funds and other educational resources from the community through creative and innovative efforts shows the achievement rate of 3/7 x 100% = 43% so that it is included in the category of lack. The performance of the School Committee in supervising education services in SD Negeri Tuntang 02 showed an achievement rate of 7/12 x 100% = 58% so that it is included in the sufficient category. The performance of the School Committee in following up complaints, suggestions, criticisms, and aspirations as well as observations on the performance of SD Negeri Tuntang 02 showed an achievement rate of 6/6 x 100% = 100%, so that it is included in the good category.